Addressing Critical Mistakes in Administering Intravenous Medications at Omdurman Military Hospital, Khartoum, Sudan - Ahmed WAM; Abdelrahman AEHE; Mohamed AA; Mohammed IO; Mustafa AMA; Ahmed ZEE; Mohamed MMT; Alghamdi FAA; Elbashir AEE; Alkubati S; Al-Sowaidi A; Dinar NMAA; et al. (International Journal of General Medicine)
Waled AM Ahmed,1,2 Amna Eltom Hajo Elsheikh Abdelrahman,3 Amal Abdelgadir Mohamed,4 Ibrahim Osman Mohammed,5 Amna Mohammed Ali Mustafa,6 Zeinab Eltayeb Elfaki Ahmed,7 Maab Mutaz Tagelsir Mohamed,8 Fahad Abdullah A Alghamdi,9 Amira EE Elbashir,10 Sameer Alkubati,11 Akram Al-Sowaidi,12 Neimat MAA Dinar,13 Abdalkhaliq Ahmed Obadi,1 Khalil A Saleh14 1Community Medicine Department, Faculty of Medicine, Al-Saeeda University, Sanaa, Yemen; 2Community Health Nursing Department, Faculty of Nursing, Al-Baha University, Al-Baha, Saudi Arabia; 3Clinical Pharmacy Department, Faculty of Pharmacy, Omdurman Islamic University, Khartoum, Sudan; 4Department of Maternity and Childhood Nursing, College of Nursing, Taif University, Taif, Saudi Arabia; 5Clinical Pharmacy Department, Faculty of Pharmacy, Gazeira University, Gazeira, Sudan; 6Department of Nursing, College of Nursing and Health Sciences, Jazan University, Jazan, Saudi Arabia; 7Obstetrics and Gynecology Department, Faculty of Medicine, Alzaeim Alazhari University, Khartoum, Sudan; 8Clinical Pharmacy Department, Faculty of Pharmacy, University of Medical Sciences and Technology, Khartoum, Sudan; 9Geriatric Care Nursing Department, Faculty of Nursing, Al-Baha University, Al-Baha, Saudi Arabia; 10Maternal and Child Health Nursing Department, Faculty of Nursing, Al-Baha University, Al-Baha, Saudi Arabia; 11Department of Medical Surgical Nursing, College of Nursing, University of Ha’il, Hail City, Saudi Arabia, and Department of Nursing, Faculty of Medicine and Health Sciences, Hodeida University, Hodeida, Yemen; 12Pharmacy Department, Faculty of Medical Sciences, Al Janad University for Science & Technology, Taiz, Yemen; 13Medical-Surgical Nursing Department, Faculty of Nursing, Al-Baha University, Al-Baha, Saudi Arabia; 14Department of Medical Surgical, College of Nursing, University of Ha’il, Hail, Saudi ArabiaCorrespondence: Waled AM Ahmed, Community Medicine Department, Faculty of Medicine, Al-Saeeda University, Sanaa, Yemen. Community Health Nursing Department, Faculty of Nursing, Al-Baha University, Sanaa, Yemen, Tel +00966508245369, Email waled-ahmed@su-edu.netObjective: Errors in the preparation and administration of intravenous medications are significant contributors to morbidity and mortality rates in medical practice. Early reporting and the implementation of preventive measures can mitigate these errors. This study aims to identify patterns and frequencies of errors in IV medication preparation and administration, along with associated factors, at Omdurman Military Hospital in Khartoum, Sudan.Methods: This observational, descriptive, cross-sectional study was conducted in the emergency department of Omdurman Military Hospital from January to May 2022. We observed 60 nurses responsible for intravenous drug preparation and administration using a pretested questionnaire and checklist on multiple occasions. The data was analyzed by SPSS and the descriptive and inferential statistics were applied.Results: Our findings reveal that 98% of the nurses reported a lack of formal training in IV drug preparation and administration. The observed preparation area was characterized as untidy in 59.6% of observations, and 52.5% were conducted in crowded environments. We identified six distinct types of errors during drug preparation, with the most common being the absence of aseptic techniques (63.2%) and the failure to check drug expiry dates before administration (99%). In contrast, five types of administration errors were reported, with the most prevalent being incorrect administration rates (68.7%) and the absence of post-administration side-effect assessments (84.8%). Additionally, 83.3% of nurses did not label the unused portion of a drug intended for the next dose.Conclusion: This study identifies a total of 11 different types of errors in IV drug preparation and administration, some of which are associated with the hospital’s work environment. The lack of formal training among 98% of the nurses stands out as a significant contributor to the increasing frequency of these errors.Keywords: medications errors, preparation, administration, intravenous, emergency